Starseed - Robinson, Spider (Ace Books, 1991)
This sequel to Stardance returns to the rarified world of Top Step, an asteroid in orbit above 21st-century Earth. There, for the price of all one's worldly possessions, humans are able to live in a vaccum indefinitely by joining with a symbiotic lifeform that provides all needed nourishment. For Rain McLeod, a 46-year-old dancer whose failing body is about to end her career, the Starseed program is the only way to continue living her dream. But for others, including several religious groups and power hungry countries back on earth, the existence of Stardancers represents a threat to all humanity. When a missile attack threatens Top Step and Morgan's lover, Robert, is implicated as a prime suspect, Rain must choose between her private dream and the greater good in a world poised on the verge of an evolutionary leap.